When genius failed : the rise and fall of Long-Term Capital Management - Lowenstein, Roger; Long-term Capital Management (Firm) (New York : Random House, 2000)
"John Meriwether, a famously successful Wall Street trader, spent the 1980s as a partner at Salomon Brothers, establishing the best - and the brainiest - bond arbitrage group in the world. A mysterious and shy midwesterner, he knitted together a group of Ph.D.-certified arbitrageurs who rewarded him with filial devotion and fabulous profits. Then, in 1991, in the wake of a scandal involving one of his traders, Meriwether abruptly resigned. For two years, his fiercely loyal team - convinced that the chief had been unfairly victimized - plotted their boss's return. Then, in 1993, Meriwether made a historic offer. He gathered together his former disciples and a handful of supereconomists from academia and proposed that they become partners in a new hedge fund different from any Wall Street had ever seen. And so Long-Term Capital Management was born.".
"When Genius Failed is the cautionary financial tale of our time, the saga of what happened when an elite group of investors believed they could actually deconstruct risk and use virtually limitless leverage to create limitless wealth."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Hedge funds -- United States